Pengembangan Evaluasi Pembelajaran Berbasis Digital Menggunakan Quizwhizzer Pada Tema 8 Subtema 2 Pembelajaran 1 - Syalshadilla, Genia Putri; Sukmanasa, Elly; Anwar, Wawan Syahiril (Peneliti.net, 2024)
This study aims to determine the development of Digital-based Learning Evaluation Using QuizWhizzer to be developed for grade IV SDN Ciheuleut 1 Bogor City and to determine the feasibility of Digital-Based Learning Evaluation Using QuizWhizzer for the learning process carried out in schools. The method used in this study uses the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). In this study, validation tests were carried out to experts. These experts are media experts, linguists, and material experts to develop and improve digital-based learning evaluations using QuizWhizzer in learning. The results of validation tests by media experts with a percentage of 97.5% with very good criteria, linguists with a percentage of 100% with very good criteria and material experts with a percentage of 84.6% with very good criteria. The results of the student response questionnaire showed results with a percentage of 81.25% with a very good category, so the results showed that learning evaluation using QuizWhizzer was very good to be developed to students and was very good to be used as a learning medium in the learning process.